2004
DOI: 10.1046/j.1572-0241.2003.04006.x
|View full text |Cite
|
Sign up to set email alerts
|

EUS-Guided Fine-Needle Aspiration of Suspected Hilar Cholangiocarcinoma in Potentially Operable Patients with Negative Brush Cytology

Abstract: These results suggest that EUS-FNA is of value as a new, less-invasive approach for tissue diagnosis of hilar strictures of unknown cause. It was technically feasible without significant risks, when other diagnostic tests were inconclusive and was able to change preplanned management in about half of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(147 citation statements)
references
References 25 publications
4
133
0
10
Order By: Relevance
“…In one study, 20% of patients with cholangiocarcinoma missed by conventional cytology were identified by FISH without affecting the specificity [28] . Several studies have evaluated the diagnostic yield of endoscopic US fine needle aspiration in patients with biliary strictures [29][30][31][32] . In one of the studies, the sensitivity and specificity of biopsy were 89% and 100%, respectively [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, 20% of patients with cholangiocarcinoma missed by conventional cytology were identified by FISH without affecting the specificity [28] . Several studies have evaluated the diagnostic yield of endoscopic US fine needle aspiration in patients with biliary strictures [29][30][31][32] . In one of the studies, the sensitivity and specificity of biopsy were 89% and 100%, respectively [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the diagnostic yield of endoscopic US fine needle aspiration in patients with biliary strictures [29][30][31][32] . In one of the studies, the sensitivity and specificity of biopsy were 89% and 100%, respectively [30] . Moreover, the planned surgical approach was changed in 27 of 44 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The only condition (either in patients with or without PSC) that does not require histological confirmation is biliary stricture associated with perihilar mass, hypertrophy-atrophy complex and vascular encasement, but this presentation is very rare. Endoscopic ultrasonography-guided fine-needle aspiration demonstrated a good diagnostic performance for discriminating benign versus malignant biliary strictures and without apparent risk of tumour seeding linked with the procedure [218][219][220][221][222] . As for iCCA, the risk of tumour seeding after transperitoneal biopsy of pCCA is based on limited evidence 223 .…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 98%
“…FNA, with or without core biopsy, is an effective method for establishing a confident morphologic diagnosis of lesions arising in or involving the liver with minimal morbidity. 12,24,25 The aspiration cytology findings of CC, both in primary tumors of the liver 12,20,24 -30 and in metastases to other anatomic locations, 31 have been described sparsely in the literature. To our knowledge, a detailed description of the cytologic appearance of the different histologic types of CC has not been published previously.…”
Section: Discussionmentioning
confidence: 99%